2005
DOI: 10.1007/s10461-005-9007-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of HIV in Women Experiencing Physical Partner Violence in Nairobi, Kenya

Abstract: As part of a study on etiology of sexually transmitted infections (STI) among 520 women presenting at the STI clinic in Nairobi, data on partner violence and its correlates were analyzed. Prevalence of lifetime physical violence was 26%, mainly by an intimate partner (74%). HIV seropositive women had an almost twofold increase in lifetime partner violence. Women with more risky sexual behavior such as early sexual debut, number of sex partners, history of condom use and of STI, experienced more partner violenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 17 publications
7
89
2
Order By: Relevance
“…Less educated women were twice as likely to experience intimate partner violence compared to the more educated women, findings that are consistent with the literature [13,14,19,28]. However, our findings appear to contradict other reports that more educated women are at increased risk of physical and sexual violence [17,22].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Less educated women were twice as likely to experience intimate partner violence compared to the more educated women, findings that are consistent with the literature [13,14,19,28]. However, our findings appear to contradict other reports that more educated women are at increased risk of physical and sexual violence [17,22].…”
Section: Discussionsupporting
confidence: 77%
“…Fourthly, we showed that women fear to test for HIV, disclose HIV results, and request to use condoms because of fear of intimate partner violence [20,21,26,29]. In a study in Kenya, women who had ever used condoms had also experienced more partner violence [28]. Intimate partner violence has also been reported following disclosure of HIV results by women to their partners [30,[47][48][49].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…IPV and abuse can also lead to unwanted sexual intercourse and, if unprotected, can lead to HIV exposure if the partner is HIV positive (Dunkle et al, 2004;Fonck, Els, Kidula, Ndinya-Achola, & Temmerman, 2005). Girls may also decide that unsafe sex presents the lesser of two risks in the face of immediate harm or threat of harm.…”
Section: Intimate Partner Violencementioning
confidence: 99%
“…3 Women of reproductive age are more vulnerable to abuse by intimate partners than by any other perpetrator. 4 Even pregnant women are victims of IPV, in Africa a strong link between IPV and HIV infection has been shown by different researchers. [4][5][6] Violence against women is a term used to collectively refer to violent acts that are primarily or exclusively committed against women.…”
Section: Introductionmentioning
confidence: 99%